ISLAM DI RUANG MAYA: MEDIA CYBER MEMBENTUK PERSEPSI DAN PRAKTIK KEAGAMAAN YANG MODERAT - Farhan Nafis, Andi Ahmad; Wahyudi AR, Nirwan (SHOUTIKA, 2025)
This study explores how cyber media, particularly social media platforms, shape moderate Islamic perceptions and practices in the digital age. Employing a qualitative descriptive approach, the research combines library research with digital observation (netnography) and applies critical discourse analysis (Fairclough) to examine religious narratives circulating on platforms such as YouTube, Instagram, and TikTok. The findings indicate that cyberspace functions both as a battleground for competing Islamic discourses and as a powerful tool for spreading moderate Islamic values. While extremist content often gains visibility due to its provocative nature, many Islamic figures have effectively used digital media to promote tolerance, balance, and inclusiveness. Moderate practices such as online sermons, digital worship, and virtual religious communities show that the digital environment can support inclusive religious life. The study concludes that cyber media is a double-edged sword—both a challenge and an opportunity in advancing moderate Islam. Future research may delve further into algorithmic impacts and digital literacy strategies in promoting inclusive Islamic discourse.